2021
DOI: 10.1093/ecco-jcc/jjab064
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase MMP-12 Promotes Macrophage Transmigration Across Intestinal Epithelial Tight Junctions and Increases Severity of Experimental Colitis

Abstract: Background and Aims Matrix Metalloproteinases (MMPs) play an important role in extracellular matrix regulation during cell growth and wound healing. Increased expression of MMP-12 (human macrophage elastase) has been reported in inflammatory bowel disease (IBD) which is characterized by the loss of epithelial tight junction (TJ) barrier function and an excessive inflammatory response. The aim of this study was to investigate the role of MMP-12 in intestinal TJ barrier function and inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 80 publications
0
36
0
3
Order By: Relevance
“…Exactly how MMP12 contributes to MMT is not known. Apart from the elastase activity, MMP12 is capable of degrading some proinflammatory mediators such as pro-TNFα [ 34 ], IFNγ [ 35 ] and CXC and CC chemokines [ 36 ]. The removal of these proinflammatory cytokines by MMP12 from the microenvironment of macrophages may promote their differentiation towards M2-like wound healing and pro-fibrotic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Exactly how MMP12 contributes to MMT is not known. Apart from the elastase activity, MMP12 is capable of degrading some proinflammatory mediators such as pro-TNFα [ 34 ], IFNγ [ 35 ] and CXC and CC chemokines [ 36 ]. The removal of these proinflammatory cytokines by MMP12 from the microenvironment of macrophages may promote their differentiation towards M2-like wound healing and pro-fibrotic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of epithelial barrier function by anti-TNF therapy may reflect mucosal healing in the setting of a dampened immune system; however, pre-clinical studies have shown that TNF signaling also modulates TJ. Many studies have shown decreased levels of intestinal TJ-consisting proteins in animal models of IBD [ 40 ], obesity, and T2D [ 41 , 42 ], with increased permeability, suggesting that a leaky pathway is responsible for LGS.…”
Section: Intestinal Barriermentioning
confidence: 99%
“…Sci. 2021, 22, x 4 of 17 of IBD [40], obesity, and T2D [41,42], with increased permeability, suggesting that a leaky pathway is responsible for LGS. Epithelial cells bind each other with tight junction, adherens junction, and desmosome.…”
Section: Intestinal Barriermentioning
confidence: 99%
“…MMP12 is an elastolytic MMP and capable of degrading extracellular matrix components (Chelluboina et al, 2018). MMP12 plays a pivotal role in inflammatory diseases, such as colitis (Nighot et al, 2021) and chronic obstructive pulmonary disease (Baggio et al, 2020). In addition, MMP12 has been regarded as a potential prognostic biomarker for ovarian cancer (Guo et al, 2020) and gallbladder cancer (Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%